A Mediational Model Explaining the Connection Between Religiosity and Anti-Homosexual Attitudes in Italy: The Effects of Male Role Endorsement and Homosexual Stereotyping. Issue 14 (6th December 2017) - Piumatti, Giovanni
ABSTRACT: This study aimed to better understand the relationship between religiosity and anti-homosexual attitudes in Italy by examining the mediation effects of male role endorsement and homosexual stereotyping. A sample of 5, 522 Italian residents (age range = 18–74) was drawn from a cross-sectional national representative survey carried out in 2011. Measures included general religiosity, male role endorsement, homosexual stereotyping, social acceptance of homosexuality, and homosexual rights endorsement. Structural equation modeling was used to test the mediational effects of male role endorsement and homosexual stereotyping on the relationship between general religiosity and attitudes toward lesbians and gay men. Results showed that both male role endorsement and homosexual stereotyping partially mediated the relationship. In a model where religiosity and both mediators positively explained anti-homosexual attitudes, male role endorsement was the strongest mediator. Endorsement of gender role beliefs and homosexual stereotyping may thus exacerbate the connection between religiosity and anti-homosexual attitudes among Italians.